Aliphatic ditopic nitrile N-oxide crosslinker: Synthesis, chemical stability, and catalyst-free crosslinking reactions. (20th January 2021) - Sogawa, Hiromitsu; Wang, Chen-Gang; Monjiyama, Shunsuke; Akae, Yosuke; Takata, Toshikazu
Abstract: Nitrile N -oxides are useful reagents and crosslinkers for catalyst- and byproduct-free 1, 3-dipolar cycloaddition reactions. The stability of nitrile N -oxides can be enhanced by introducing bulky substituents, whereas their reactivity decreases concomitantly. Herein, an isolatable aliphatic ditopic nitrile N -oxide was synthesized and applied to catalyst-free crosslinking of unsaturated bond-containing polymers. By decreasing the steric hindrance around the nitrile N -oxide moiety compared with a related crosslinker previously developed in our group, the operating temperature of the crosslinking reaction could be lowered. Efficient crosslinking of natural rubber (NR) was achieved at 40 °C in chloroform to give crosslinked NR without formation of byproducts. Furthermore, polyacrylonitrile and nitrile butadiene rubber can be used as the scaffolds for efficient catalyst- and solvent-free crosslinking reactions. Graphical abstract: Image 1 Highlights: Novel isolatable aliphatic ditopic nitrile N -oxide was synthesized. Efficient catalyst- and solvent-free crosslinking of unsaturated bond-containing polymers was successfully achieved. The decrease of the steric hindrance allowed to lower the operating temperature of crosslinking reaction.